Percakapan Mandarin praktis Tan Tiong Hwat; penyunting, Dwi A. Santoso; ilustrasi, Suharyanto, Esvandiari Sant - TAN, TIONG HWAT; A. Santoso, Dwi; Sant, Esvandiari; Suharyanto (Puspa Swara, 2005)
iv, 153 hlm ilus 25 cm